Unexplained First Trimester Intrahepatic Cholestasis of Pregnancy: A Case Report and Literature Review - Anastasia A. Salame; Mohammad J. Jaffal; Marco A. Mouanness; Amal R. Nasser Eddin; Labib M. Ghulmiyyah (Case Reports in Obstetrics and Gynecology)
Intrahepatic cholestasis of pregnancy (ICP) is a condition that usually affects the 3rd trimester-pregnant women and is associated with adverse pregnancy outcomes. We present a 31-year-old G2P1 patient with symptoms of ICP as early as 10 weeks of gestation (WG). Her pruritis was initially attributed to eczema. Due to the intensity of her discomfort and failure of topical treatment, ICP was suspected, total bile acid salt levels were taken and ursodeoxycholic acid was subsequently started at 18 WG. The patient was followed closely during her pregnancy to adjust the dose of the medication accordingly. Induction of labor was performed at 37 WG without complications. This case demonstrated the importance of clinical suspicion in the setting of such symptomatology in order not to miss or delay treatment of threatening conditions such as ICP.